Effects of silver nanoparticle exposure on germination and early growth of Pinus sylvestris and Alnus subcordata - Bayramzadeh, Vilma; Ghadiri, Maryam; Davoodi, Mohammad Hossein (Penerbit Universiti Kebangsaan Malaysia, 2019)
The possible ecological toxicity of silver nanoparticles (AgNP) was evaluated based on germination and growth characteristics of Pinus sylvestris and Alnus subcordata. Seeds were exposed to different concentrations of AgNP in soil (0, 10, 20, 40, 80 and 100 mg/kg) and aqueous suspension (0, 10 and 20 mg/L). Then, seed germination percentage (GP%), speed of germination (S.G), seedling length (SL), as well as fresh and dry weights (FW and DW) were measured. The results showed that low concentration of AgNP (under 80 mg/kg) could be used without detrimental effects on the germination characteristics of P. sylvestris in the soil. Nevertheless, inhibitory effect of AgNP was observed at 10 mg/L for P. sylvestris in aqueous suspension. The dissimilar results in soil and aqueous suspension were due to the organic matters and clay minerals in the soil. There was no significant difference (p<0.01) among the treatments of A. subcordata, not only in soil but also in the aqueous suspension.